Public R&D subsidies and employment growth: Microeconomic evidence from Finnish firms - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2008)
This study empirically explores whether the public financial support for entrepreneurial R&D affects employment growth at the firm level. The data from the Finnish companies suggests that the firms that have received public R&D funding have not generally witnessed any greater employment growth than other companies. However, we find that the public R&D support targeted to the certain types of R&D activities notably contribute to the creation of new jobs: employment in those firms that have received public funding for the R&D projects targeted to the new business areas has clearly grown relatively more than in other companies. The relationship between the firm's total innovation and employment growth is not statistically significant.
Keywords: J23; L10; O33; O38; 330; public R&D subsidies; technology policy; employment growth; Forschungs- und Technologiepolitik; Forschungssubvention; Innovation; Beschäftigungseffekt; Wirkungsanalyse; Finnland